Organizational Development with Six-Box Weisbord's Diagnostic Model - Ratri Kurnia Ihsani; Muhammad Nur Syuhada (LLDIKTI Wilayah X, 2020)
This research was conducted to see the problem in one automotive company in Indonesia. This research was carried out with the Six Box organizational diagnostic method. This method will reveal the company's conditions in the aspects of purpose, structure, reward, helpful mechanism, leadership, and relationship. Retrieval of data using interviews with four sources. The results show that there are areas that need to be developed related to aspects of helpful mechanism. The researcher recommends updating the position description in the position of Branch Manager and the new design of the development program for the managerial level, the Future Leader Development Program.